Nasal Haemangioendothelioma: one case report - Sousa e Castro, Sandra (2010)
Haemangioendotheliomas  belong  to  a  large  and  heterogeneous group of vascular  tumours that  usually involves long bone or soft tissue. However, there are cases of head and neck involvement.  Nasal  haemangioendotheliomas  are  extremely rare, with few cases published in the world literature. These neoplasms are considered borderline lesions, varying between fully benign entities, such as fusocelular haemangioendothelioma, and the malignant ones, such as haemangiosarcoma.The authors present a case of a 78-years-old woman with repeated episodes of epistaxis. The examination showed a polypoid lesion located on the right nasal cavity, which was submitted to biopsy. Microscopic examination showed a fusocelular haemangioendothelioma.  An  endoscopic  surgical  approach was performed. After a 12-month follow-up period the patient is disease-free, without any local or distant recurrence.